2022
DOI: 10.7196/sajcc.2022.v38i1.517
|View full text |Cite
|
Sign up to set email alerts
|

Professional quality of life of nurses in critical care units: Influence of demographic characteristics

Abstract: Background. Professional quality of life, measured as compassion satisfaction, is a prerequisite for nurses working in intensive care units where patients rely on their care. Nurses who experience compassion satisfaction, or good professional quality of life, engage enthusiastically with all work activities and render quality patient care. In contrast, compassion fatigue eventually leads to disengagement from work activities and unsatisfactory patient outcomes. In this study, we described the demographic facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 35 publications
2
9
1
Order By: Relevance
“…Regarding BOS prevalence among ICU nurses during the COVID-19 pandemic, seven studies [37,38,[40][41][42][43][44] provided evidence of the presence of BOS symptoms in the ICU nurses participating in the studies, thus, supporting answers to the first research question of the present review. In the Belgian context [37], 68% out of the 1100 participating ICU nurses showed BOS symptoms.…”
Section: Prevalence Of Bos Among Icu Nurses During the Covid-19 Pandemicsupporting
confidence: 74%
See 4 more Smart Citations
“…Regarding BOS prevalence among ICU nurses during the COVID-19 pandemic, seven studies [37,38,[40][41][42][43][44] provided evidence of the presence of BOS symptoms in the ICU nurses participating in the studies, thus, supporting answers to the first research question of the present review. In the Belgian context [37], 68% out of the 1100 participating ICU nurses showed BOS symptoms.…”
Section: Prevalence Of Bos Among Icu Nurses During the Covid-19 Pandemicsupporting
confidence: 74%
“…In a Turkish sample composed of 116 intensive care nurses, Kurt Alkan et al [41] found a mean total score of burnout of 50.75 out of 70, as well as a significant positive correlation between nurses' burnout and fear of COVID-19. As shown by Ndlovu et al [42], the majority of the 225 involved South African nurses working in critical care units during the first wave of COVID-19 experienced moderate-to-high burnout, that is, 26.6% scored below 43 (low burnout), 46.1% scored between 43 and 56 (moderate burnout), and 27.3% scored higher than 56 (high burnout). Among 140 nurses working in Iranian ICUs, Omidi et al [43] found that 45% of them showed moderate-to-high emotional exhaustion, 43.6% showed moderateto-high depersonalization, and 5% reported low personal accomplishment.…”
Section: Prevalence Of Bos Among Icu Nurses During the Covid-19 Pandemicmentioning
confidence: 93%
See 3 more Smart Citations